How educational ideologies are shaping global society : intergovernmental organizations, NGO's, and the decline of the nation-state - Spring, Joel H. (Sociocultural, political, and historical studies in education., 2004)
Joel Spring explores three major international educational ideologies that are shaping global society: neo-liberal educational ideology, human rights education, and environmentalism. These changes are fueling a clash between the ideas of free-market and consumer-based neo-liberals and those of human rights and environmental educations.